Motif dan Identitas Keagamaan dalam Persebaran Meme Hadis Tashabbuh di Media Sosial - Muhammad Zuhri Abu Nawas; Muhsin Mahfudz; Amrullah Harun; Muh. Rizaldi (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2022)
This paper examines the expression of the Muslim community in narrating hadith tashabbuh (imitation) in the form of memes. It aims to analyze the form and tendency of the memes through social media as well as the motive behind its creation. Using the theory of reception and constructivism with discourse analysis framework, this article argues that: first, the resonance of hadith tashabbuh is echoed in three forms of memes that spread across social media, namely on the lifestyle, new year celebrations, and birthdays. Second, the motive behind this phenomenon is an effort to affirm the identity and truth claims of the religious ideology of the textualist-fundamentalist group. The affirmation is expressed by claiming to be a group that follows the Prophet’s sunna, while justifying others as a group that does not follow the sunna. On the other hand, there is also a motive in revitalizing and reactualizing hadith that in line with the group’s form of hadith understanding. In the end, it implied for the creation of contestation over the meaning of the hadith tashabbuh to various aspects of life which then affects the religious paradigm of the Muslim community.